Minimally Invasive Glaucoma Surgery - Sng, Chelvin C. A.; Barton, Keith (Springer Nature Singapore : Imprint: Springer, 2021)
The book is provided open access under a CC BY 4.0 license. This book covers all aspects of minimally invasive glaucoma surgery (MIGS) and provides detailed information on each MIGS device, including its mechanism of action; patient selection; implantation techniques; post-operative management; and a review of the existing literature. Step-by-step descriptions are provided for the surgical technique used in implanting each MIGS device, accompanied by clear photographs of each surgical stage. Other areas covered include intra-operative gonioscopy (with tips on optimising the view of the anterior chamber angle) and the management of the intra-operative and post-operative complications. Essential information on the anatomy and physiology of the different aqueous outflow pathways is also included. A separate chapter addresses the introduction of MIGS globally, including the consideration of different reimbursement environments and the different types of glaucoma, e.g. angle closure glaucoma. This book will assist both glaucoma surgeons and general ophthalmologists in overcoming the learning curve involved in performed MIGS, by providing valuable and practical clinical pearls.